2022
DOI: 10.1002/cche.10577
|View full text |Cite
|
Sign up to set email alerts
|

Tortillas made from nixtamalized maize and extruded chickpea flours: A product with improved in vitro nutritional and antihypertensive properties

Abstract: Background and Objectives: In this study, tortillas with improved in vitro nutritional and antihypertensive properties were developed using flours produced from nixtamalized maize (NixM) and extruded chickpea (ExtCP). The aims were (1) to find the optimal extrusion conditions to produce optimized ExtCP flour with high values of antioxidant activity (AoxA), total phenolic compounds (TPC), and in vitro protein digestibility (IVPD), and (2) to evaluate the addition effect of 30% of optimized ExtCP flour over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The experimental values of WAI, WSI, IVPD, TPC, and AoxA of OESBF were similar to the predicted values shown in Figure 3, indicating that the optimal conditions of extrusion were appropriated and reproducible. The application of food processes such as extrusion, under optimal conditions, when it has been optimized to obtain the maximum values of some properties such as WAI, WSI, IVPD, TPC, and AoxA, allows to obtain mainly extruder flours with high values of these properties (Bon-Padilla et al, 2022). Extruded flours are suitable for developing new functional foods with healthy benefits.…”
Section: Issn Online 2007-9621mentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental values of WAI, WSI, IVPD, TPC, and AoxA of OESBF were similar to the predicted values shown in Figure 3, indicating that the optimal conditions of extrusion were appropriated and reproducible. The application of food processes such as extrusion, under optimal conditions, when it has been optimized to obtain the maximum values of some properties such as WAI, WSI, IVPD, TPC, and AoxA, allows to obtain mainly extruder flours with high values of these properties (Bon-Padilla et al, 2022). Extruded flours are suitable for developing new functional foods with healthy benefits.…”
Section: Issn Online 2007-9621mentioning
confidence: 99%
“…Sánchez-Magaña et al (2022),Gámez-Valdez et al (2021), andLeón-López et al (2019) reported an increase in AoxA after extrusion in quinoa, amaranth, and defatted chia, respectively. They attributed this increase in AoxA to the release of antioxidant phenolic compounds during the extrusion process Bon- Padilla et al (2022). reported an increase in AoxA in extruded chickpea flour.…”
mentioning
confidence: 99%